Distribution of hepatitis A antibodies in United States blood donors - Tejada-Strop, Alexandra (Transfusion, 2018)
BACKGROUND: Recently, there has been an increase in the number of hepatitis A outbreaks in the United States. Although the presence of HAV RNA in blood donors is known to be very low, HAV antibody prevalence in this population is unknown. METHODS: Samples from 5001 US blood donors collected primarily in the Midwestern US in 2015 were tested for the presence of HAV IgG antibodies using chemiluminescent microparticles immunoassays on the ARCHITECT platform (Abbott Laboratories). RESULTS: The overall prevalence of IgG anti-HAV was 60%. Only one specimen was IgM anti-HAV positive for an incidence of 0.02%. IgG anti-HAV prevalence among donors 16 to 19 years was 67%, dropped to 54% among donors aged 40 to 49 years and increased to 70% among donors aged 80 to 93 years. No differences were seen by sex with overall IgG anti-HAV prevalence of 61% and 60% for males and females, respectively. Among the five states (Illinois, Indiana, Kansas, Kentucky, and Missouri) with the highest number of donors tested, IgG anti-HAV prevalence in Missouri (65%) was significantly higher (P <0.01) than that in Illinois (52%) or Kentucky (59%). No other significant differences between states were noted. CONCLUSIONS: This study demonstrates the overall high rates of IgG anti-HAV in US blood donors with the low associated risk of HAV transfusion transmission is likely the result of low incidence and effective vaccination.